Usulan Agenda WTO Pemerintah Baru - Jhamtani, Hira (UI Scholars Hub, 2004)
Indonesia became a member of the World Trade Organization (WTO) in 1994 without prior research on the benefits and adverse impacts, and the rights and obligations involved in taking such a major policy measure. The government also did not prepare human resources and other capacities needed to take advantage of being a WTO member. Consequently, Indonesia is trying hard to comply with WTO rules but does not have the capacity to tap the opportunities provided by trade liberalization. This article aims to explain the challenges and problems faced by Indonesia related to the WTO issue, especially about the problem of Indonesia’s position in the WTO. Remembering it is only recently that Indonesia began actively strife for a better bargaining position at the WTO negotiation, the article also recommends seven steps to improve the situation, including statements that request the new government to take immediate practical steps involving briefing about WTO to the new ministers, study on the impacts of WTO, establish a strong WTO negotiating team, perhaps in the office of the president, and to halt all liberalization policies until national trade and industrial master plans and positions are established.